2003
DOI: 10.1002/ejoc.200390127
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pyrolytic and Kinetic Behaviour of β,δ′‐Dioxo‐Stabilised Phosphorus Ylides: Convenient Preparation of γ,δ‐Alkynyl Ketones and 2,3‐Functionalised Butadienes

Abstract: Both ketone‐ and ester‐stabilised phosphorus ylides undergo Michael addition to vinyl ketones to give the β,δ′‐dioxo ylides 3 and 5, respectively, although in the latter case careful temperature control is required to avoid an undesired side‐reaction. Under conditions of flash vacuum pyrolysis at 650 °C the ylides 3 generally undergo Ph3PO extrusion to afford the γ,δ‐alkynyl ketones 14, although these are found to partly undergo a secondary fragmentation. In contrast, the ylides 5 react under the same conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In these studies, no attempt was made to examine the kinetics of the processes involved and indeed until recently the thermolysis of phosphorus ylides has not previously been examined from the kinetic point of view [4]. We recently reported kinetic data for the thermolysis of a range of ␤,␦-dioxo ylides [5], and in Part 1 of this series [6] we presented a detailed kinetic study of substituted benzoyl/arylcarbamoyl ylides and their thiocarbamoyl analogues. Although this did give useful mechanistic information, the process involved turned out to be simply reversion to the starting materials from which the ylides were formed.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, no attempt was made to examine the kinetics of the processes involved and indeed until recently the thermolysis of phosphorus ylides has not previously been examined from the kinetic point of view [4]. We recently reported kinetic data for the thermolysis of a range of ␤,␦-dioxo ylides [5], and in Part 1 of this series [6] we presented a detailed kinetic study of substituted benzoyl/arylcarbamoyl ylides and their thiocarbamoyl analogues. Although this did give useful mechanistic information, the process involved turned out to be simply reversion to the starting materials from which the ylides were formed.…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism is available (Scheme ) which provides an adequate account of the observed products of pyrolysis of the ylides under consideration. It involves conformational pre‐organization of the ylide, and a four‐membered TS leading to the products of thermal elimination 15–17. In the ylide form, the α ‐ketone/thione (CX) group is arranged syn to the phosphonium moiety; and in the resonance dipolar enolate form, the oxide/sulfide moiety is consequently arranged in a conformation ideal for the subsequent extrusion of triphenylphosphine oxide (Ph 3 PO) and its sulfide analog (Ph 3 PS) 9, 15–22.…”
Section: Resultsmentioning
confidence: 99%
“…Replacement of one of the (H) atoms particularly by an electron‐withdrawing group (EWG) leads to molecular stability, and the planar conformation at (C) provides the ideal geometry for conjugation and hyperconjugation effects to dominate the molecular reactivity of stabilized triphenylphosphonium methylides. Our pioneering studies on the kinetics of the gas‐phase pyrolysis of these ylides and their arsonium analogs have shown that the stabilized monosubstituted phosphonium ylide is less reactive than the disubstituted counterparts, and that the monosubstituted arsonium analog changes mechanism from a dipolar transition state (TS) to a pathway involving a reactive carbene intermediate 1, 16–20. The present study investigates the kinetics and mechanism of the thermal gas‐phase elimination reactions of fourteen α ‐carbonyl‐ and thiocarbonyl‐stabilized triphenylphosphonium methylides to assess the magnitude of change in reactivity with change in the structure of the stabilizing ketone/thione moiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latent nucleophilicity of the title compound enables Michael addition reactions. For example, Bestmann 28 and Aitken 29 have shown that high yields of conjugate addition products can be obtained when acetylmethylenetriphenylphosphorane is reacted with a variety of enones in toluene at reflux (eq 25). …”
Section: Ylide Functionalizationmentioning
confidence: 99%